Does hemoglobin mass increase from age 16 to 21 and 28 in elite endurance athletes? - Steiner, T.; Wehrlin, J. P. (Medicine & Science in Sports & Exercise, 2011)
Purpose: It is unclear if hemoglobin mass (Hbmass) and red cell volume (RCV) increase in endurance athletes with several years of endurance training from adolescence to adulthood. The aim of this study, therefore, was to determine with a controlled cross-sectional approach whether endurance athletes at the ages of 16, 21, and 28 yr are characterized by different Hbmass, RCV, plasma volume (PV), and blood volume (BV).